Assessment on Methods of Capturing Knowledge: A Study - Dash, Bedarata (Journal of Advanced Research in Library and Information Science, 2020)
Knowledge Capture through a variety of techniques used to elicit facets technical knowledge such that insights, experiences, social networks and lesson learned which can be shared to mitigate organizational knowledge loss. This paper aims to explore how organizations adopted different methodology to capture the knowledge. Using a case study method, attempts have been made to know how all the knowledge centres used to have dedicated resources to detect and obtain external knowledge and encourage personnel to participate project team with external experts. The purpose of this article is to explore IBM, INFOSYS, TCS and WIPRO capacity to absorb and capture knowledge as a prior condition to the successful adoption of innovations and entrepreneurial growth. The findings highlight the use of knowledge whether captured from external sources or internal sources being done through a sharing mechanism within the organisation.